Connecting networks : characterising contact by measuring lithic exchange in the European neolithic - Kerig, Tim; Shennan, Stephen (Archaeopress Publishing Ltd, 2015)
This volume brings together a group of peer reviewed papers, most of them presented at a workshop held at the Institute of Archaeology, University College London. The event took place on 15-17 October 2011 and was part of the European Research Council (ERC) funded project Cultural Evolution of Neolithic Europe (EUROEVOL 2010-2015).